2019
DOI: 10.3892/etm.2019.8253
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy, safety and prognosis of treating neurological deficits caused by spinal tuberculosis within 4�weeks' standard anti‑tuberculosis treatment: A single medical center's experience

Abstract: The present study aimed to retrospectively analyze the safety and efficacy of the early surgical management of thoracic tuberculosis (TB) in patients with neurological deficits. The medical data of patients with thoracic TB exhibiting neurological deficit in the Chest Hospital of Hebei Province were retrospectively reviewed. A total of 234 cases, including 123 males and 115 females, were recruited in the present study. Their pre- and postoperative neurological deficit and pain levels were assessed using the 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 21 publications
0
15
0
2
Order By: Relevance
“…Zhang et al [ 19 ] stated that surgery could be performed after a significant decrease in ESR and CRP has been observed. Jia et al [ 20 ] conducted a study that compared early (< 4 weeks) and non-early surgery (≥ 4 weeks) for the treatment of spinal TB with neurological deficit. They recommended early surgical management due to the superior improvement of neurological status in the early surgery group.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al [ 19 ] stated that surgery could be performed after a significant decrease in ESR and CRP has been observed. Jia et al [ 20 ] conducted a study that compared early (< 4 weeks) and non-early surgery (≥ 4 weeks) for the treatment of spinal TB with neurological deficit. They recommended early surgical management due to the superior improvement of neurological status in the early surgery group.…”
Section: Discussionmentioning
confidence: 99%
“…(1) If the cortical bone is relatively complete, the stability of the spinal anterior column may be not seriously destroyed. (2) The posterior pedicle screw system is a type of three-column fixation that can effectively maintain the stability of the spinal anterior column and is conducive to bone graft fusion. 22 Therefore, we consider that the indications for one-stage posterior debridement, nonstructural bone graft repair, and internal fixation for single-segment lumbar TB are as follows: (1) progressive aggravation of neurological impairment or local instability or kyphosis deformity; (2) singlesegment lumbar TB with (a) bony (a-d) Preoperative computed tomography showed that the L5 vertebral body and the L2/3 intervertebral disc were destroyed (<50% of the height of the vertebrae).…”
Section: Discussionmentioning
confidence: 99%
“…1 Spinal TB mostly occurs in the lower thoracic and lumbar vertebrae, resulting in vertebral body destruction, collapse, kyphosis, and even paralysis. 2 Surgical treatment of TB is mainly suitable for patients with spinal instability, severe kyphosis, or impaired neurological function. 3 Radical debridement is the key to successful spinal TB surgery because it helps to control TB lesions, improve the effect of anti-TB chemotherapy, promote bone graft fusion, and reduce the risk of TB recurrence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang et al [18] stated that surgery can be performed after a signi cant decrease of ESR and CRP has been observed. Jia et al [19] conducted a study of comparison of early (<4 weeks) and non-early surgery (≥ 4 weeks) for the therapy of spinal TB with neurological de cit, they found early surgical management is recommended because of superior improvement of neurological status in the early surgery group.For our series, early operation was de ned as operation carried out within 3 weeks of paraparesis and paraplegia. We found signi cant neurological function improvement together with other positive indexes after early surgery.…”
Section: Discussionmentioning
confidence: 99%